Meningkatkan Daya Saing UMKM Tempe: Inovasi Kemasan dan Edukasi Pemasaran di Desa Dolok Sagala - Titin Elfrida Situmorang; Suwadi Suwadi; Yenni Arfah; Rika Zalukhu; Abednego Ketaren; Nursaimatussaddiya Nursaimatussaddiya; Azril Syahputra; Rahma Yanti Batubara; Putri Andria (STIE Bina Karya, 2026)
This community service program was conducted in Dolok Sagala Village, Dolok Masihul District, Serdang Bedagai Regency, as part of the Community Service Program (KKN) of STIE Bina Karya Tebing Tinggi. The program focused on the theme